Elder psychological abuse: narrative review of evidence and gaps in research - Casella, Claudia; Marisei, Mariagrazia; Gloria, Lucia; Carrella, Maria; Di Donna, Gaetano; Di Lorenzo, Pierpaolo (Frontiers in Public Health, 2025)
IntroductionElder abuse is a substantial global public health and human rights problem, certainly one of the lesser known and studied forms of violence whose impact must not be overlooked because of its significant representation worldwide. Although psychological abuse has been found to be the most frequent form of abuse, specific knowledge regarding this form of violence is still lacking.Materials and methodsThe PubMed database was searched using a combination of search terms related to older people, emotional and psychological violence and abuse and exclusion, as much as possible, of physical abuse.ResultsTen studies met inclusion criteria, representing diverse geographical contexts (United States, Poland, Taiwan) and settings (community, institutional). The analysis of the articles showed the absence of a shared definition, lack of structural conceptualization and extreme variability in the prevalence of the phenomenon reflecting the variability of definitions and socio-cultural heterogeneity and reduced reporting rates.Discussion and conclusionsThe available literature on Elder Psychological Abuse is still limited and fragmented, with a small number of studies dedicated to this specific topic, the absence of a shared definition and the lack of standardized categorization and assessment tools. These elements underscore the need for further research to explore the phenomenon in depth, promoting the development of a single definition and reliable tools for its identification and classification.